Pemurnian Bioetanol Hasil Fermentasi Nira Nipah Menggunakan Proses Destilasi-Adsorpsi Pada Variasi Rasio Adsorben Dengan Modifikasi - Yenti, Silvia Reni; Yuliana, Yuliana; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is used in the fuel mixture to the vehicle must be anhydrous so as not to cause corrosion in the engine, so that bioethanol should have a grade of 99% -100%. One of the main problems in the process of making bioetanol is the process of separation water with ethanol to get ethanol dry ( 99,95 % ). Purification of ethanol is usually done by distillation, but the distillation process has the disadvantage because of the azeotrope so hard to get dry ethanol. One method that is cheaper and easier is by distillation-adsorption using porous media. This study aims to obtain bioethanol from nypa using distillation purification process-adsorption using bentonite pellets, to obtain comparative data on the adsorption ability of bentonite pellets and data additions optimum starch and characterize the physical properties of bioethanol and qualitative test with GC. This research was conducted in several stages of the preparation of bioethanol, activation of bentonite, bioethanol purification by distillation-adsorption process, and product analysis. Variations of ratio adsorbent: bioethanol 1: 2, 1: 3, and 1: 4, and variations of the addition of starch varied namely 30, 35, 40 and 45% of the weight of bentonite, process temperature 78 °C, the activation of bentonite in physics. From the research results, obtained by the process of distillation-optimum adsorption with activated bentonite adsorbent physics with the addition of 35% starch with a ratio of 1: 2. Ethanol levels increased from 96% to 99.8% volume.Keywords: Bentonite, bioethanol, distilation- adsorption process, nypa, starch